Crushing behavior of foam filled steel extrusion / Al Emran Ismail - Ismail, Al Emran (2008)
The concern of vehicle structural integrity and safety is given highly considerable amount of research and development by engineers and scientist world wide. Weight reduction of structures without compromising the structural durability is the important aspect because weight is strongly related to fuel consumption. In this work, rigid polyurethane foam is used to fill into steel extrusions. Different foam density is used to reinforce the steel tubes and at the same time different steel wall thickness also adopted to study the crushing behavior under quasi-static compression loading loaded at different angles. Force versus displacement of each column condition is recorded automatically, compared and analyzed. The area under the curve represent the energy absorbed by the column and the column length is properly designed to prevent buckling which will be resulted catastrophic failure leading to low energy absorption capability. Then, the final crushed columns are analyzed to study the correlation with the crushing characteristics. It is found that the energy absorption increased when increasing the foam density but when the tube wall reached a maximum thickness, the foam density no longer affected to increase the energy absorption.